Microwave‐Induced In Situ Synthesis of Zn2GeO4/N‐Doped Graphene Nanocomposites and Their Lithium‐Storage Properties. Issue 19 (11th March 2013) - Zou, Feng; Hu, Xianluo; Sun, Yongming; Luo, Wei; Xia, Fangfang; Qie, Long; Jiang, Yan; Huang, Yunhui
Abstract Zn2GeO4/N‐doped graphene nanocomposites have been synthesized through a fast microwave‐assisted route on a large scale. The resulting nanohybrids are comprised of Zn2GeO4 nanorods that are well‐embedded in N‐doped graphene sheets by in situ reducing and doping. Importantly, the N‐doped graphene sheets serve as elastic networks to disperse and electrically wire together the Zn2GeO4 nanorods, thereby effectively relieving the volume‐expansion/contraction and aggregation of the nanoparticles during charge and discharge processes. We demonstrate that an electrode that is made of the as‐formed Zn2GeO4/N‐doped graphene nanocomposite exhibits high capacity (1463 mAh g−1 at a current density of 100 mA g−1), good cyclability, and excellent rate capability (531 mAh g−1 at a current density of 3200 mA g−1). Its superior lithium‐storage performance could be related to a synergistic effect of the unique nanostructured hybrid, in which the Zn2GeO4 nanorods are well‐stabilized by the high electronic conduction and flexibility of N‐doped graphene sheets. This work offers an effective strategy for the fabrication of functionalized ternary‐oxide‐based composites as high‐performance electrode materials that involve structural conversion and transformation.